Set-Membership Filtering for 2-D Systems Under Uniform Quantization and Weighted Try-Once-Discard Protocol - Li, Meiyu; Liang, Jinling; Qiu, Jianlong (IEEE transactions on circuits and systems. II, Express briefs, 2023)
This brief studies the issue of non-fragile set-membership filtering for two-dimensional systems with uniform quantization and communication constraint. The signal transmission is adjusted by using the weighted try-once-discard (WTOD) protocol to lessen the communication burdens and increase the data scheduling flexibility. The main objective of this brief is to design a non-fragile set-membership filter for the addressed system such that, in the presence of the uniform quantization and the WTOD protocol, the filtering error is restricted to certain ellipsoidal region. A sufficient condition for the existence of the desired set-membership filter is given in the form of a set of recursive matrix inequalities. Subsequently, an optimisation problem subject to certain inequality constraint is presented to obtain the local minimum ellipsoid in the sense of matrix trace. Finally, effectiveness of this filtering strategy is checked by a numerical example.